Strategic Business Units and SWOT Application in Business Management Strategy - Rachma, Amalia Fadilla; Islamiyah, Nuril; Destasya, Annola; Chamariyah (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to explain the analysis of the implementation of strategic management in SMPT Daarul Muttaqien through a review of the Strategic Unit Business (SBU) and SWOT analysis. In the application of SBU, Glueck, Hunger and Wheelen theory is used, while SWOT analysis uses Fred R. David matrix theory. In this study, the method used is qualitative descriptive with secondary data collection using observation and interview techniques. The results of the study show that Daarul Muttaqien Integrated Islamic Boarding School Foundation in the SBU analysis is more suitable to use the Combination strategy while still taking advantage of the advantages but must adapt to developments in the world of education. In the SWOT analysis, the management strategy that can be used is Progressive Strategy, namely daring to take advantage of the strengths it has and take the business opportunities it faces.